Humanistic Digital Management Model (HDMM): Integrating Ethical Leadership and Digital Ethics - Odjie Samroji (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Digital transformation improves efficiency but risks dehumanization through datafication, opaque algorithmic decisions, and diluted accountability. This qualitative–conceptual article synthesizes humanistic management, ethical leadership, and digital ethics into a Humanistic Digital Management Model (HDMM). Ethical leadership functions as a value-internalization and accountability mechanism; digital ethics provides design and oversight principles (privacy, transparency, non-discrimination, security); and organizational culture moderates the translation of values/principles into practice. Grounded in a philosophy-of-science triad (ontology, epistemology, axiology), the paper advances four propositions, operational guidance, and managerial implications—algorithmic impact assessment, digital codes of ethics, and culture-building routines that safeguard human dignity. We outline measurement directions and empirical designs to validate HDMM and support human-centered organizing.